Effect of Regulator of G Protein Signaling Proteins on Bone - Yuan, Gongsheng; Yang, Shuying (Frontiers in Endocrinology, 2022)
Regulator of G protein signaling (RGS) proteins are critical negative molecules of G protein-coupled receptor (GPCR) signaling, which mediates a variety of biological processes in bone homeostasis and diseases. The RGS proteins are divided into nine subfamilies with a conserved RGS domain which plays an important role in regulating the GTPase activity. Mutations of some RGS proteins change bone development and/or metabolism, causing osteopathy. In this review, we summarize the recent findings of RGS proteins in regulating osteoblasts, chondrocytes, and osteoclasts. We also highlight the impacts of RGS on bone development, bone remodeling, and bone-related diseases. Those studies demonstrate that RGS proteins might be potential drug targets for bone diseases.